Validitas Media Pembelajaran Interaktif Berbasis Autoplay dalam Mata Pelajaran PAI dan Budi Pekerti untuk Sekolah Dasar - Firza Erisa; Sirajul Munir; Lita Sari Muchlis; Annisaul Khairat (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Based on the characteristics of elementary school students who are in line with Pieget's theory of development, children aged 7-11 years are in the concrete operational phase. Grade II students at SDN 04 Balimbing have visual and kinesthetic learning styles. So it requires learning media that is concrete and aligned with the characteristics of students, especially in PAI subjects and Taharah material. The aims of this study were (1) to develop autoplay-based interactive learning media for PAI subjects and Class II SD Taharah subject matter and (2) to determine the validity of autoplay-based interactive learning media. The research method used is research and development using the ADDIE development model. Stages of research using the ADDIE model. The results showed that autoplay-based interactive learning media for PAI subjects and morals in thaharah material were stated to be very valid with an average of 0.847. Validation was carried out by expert lecturers and Islamic education and ethics subject teachers. Based on these results, interactive learning media based on autoplay can be used in learning.